Market reactions and the role of corporate governance in mergers & acquisitions : evidence from Indian firms. - Lye, Charmian Hui Qin. (2010)
The importance of Merger and Acquisitions (M&A) as a strategy to pursue organizational objectives is evident by its increase over the years. This paper aims to analyze the M&A landscape in India. Particularly, we want to study how the strategic M&A’s decision of acquiring firms is influenced by their pre-acquisition characteristics and how the market reacts to such a decision. Five corporate governance factors namely, proportion of independent directors, board size, Chairman-CEO duality, board activities, CEO tenure and number of board meetings were used as predictors to determine whether the company is likely to pursue a focused or diversified acquisition. This is coupled with three financial factors: leverage, cashflow and profitability as control variables. The final result of this study may provide valuable insights to managers in ensuring a balanced focus on these factors in managing a firm. The statistical analyses reaffirmed our main hypothesis that focused acquisitions lead to positive market reaction. In addition, companies with high proportion of independent directors, Chairman-CEO duality, high leverage and high profitability are more likely to conduct focused acquisition.